Peran Fisioterapi pada Pemulihan Fungsi Gerak dan Jaringan Kulit Pasien Amputasi Ibu Jari Kanan Post Flap: Studi Kasus - Rafika Hasmi Lefia; Wijianto Wijianto; Nilam Nur Hamidah (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2026)
Thumb amputation causes a significant decrease in hand function, requiring reconstructive procedures such as flaps and physiotherapy rehabilitation to optimize recovery. The aim of study was to determine the role of physiotherapy in a 54-year-old male patient after amputation of the right thumb who underwent flap surgery. This study employed a case study method with a descriptive-analytical approach. The physiotherapy program provided included Transcutaneous Electrical Nerve Stimulation (TENS), Ultrasound Therapy, skin massage, and active-resisted workouts for 4 weeks with each session lasting 20 minutes. Evaluation assessments used numeric rating scale (NRS), goniometry, Manual Muscle Testing (MMT), tissue elasticity examination, and Patient-Rated Wrist Evaluation (PRWE). The results of the study found that the physiotherapy interventions provided included TENS, Ultrasound Therapy, skin massage, and active-resisted workouts, which were proven to provide significant benefits in reducing pain, increasing Range of Motion (ROM), increasing muscle strength, and increasing scar tissue elasticity. This case study demonstrates that physiotherapy plays a crucial role in accelerating recovery, improving hand function, and supporting the success of tissue reconstruction procedures in post-flap thumb cases.